Contemporary Australian Archetypes: Different People, Different Needs - Rodgers, B; Berry, H; Caldwell, T; Butterworth, P (My University, 2008)
This report presents the results of the first of a two-phase program of research being conducted from 2005 to 2007 investigating types of people living in Australian communities. This is the first Australian study to use cluster analytic techniques to explore how a wide variety of sociodemographic, psychosocial and health factors combine and find expression in the lives of Australians. The analysis has been based on a large, nationally representative dataset with a social policy focus. As a result, the findings are broadly applicable to all Australians, and are directly relevant for social policy purposes.
Department of Families, Housing, Community Services and Indigenous Affairs, Social Policy Research Paper
Social Policy Research Papers
Keywords: Social Capital; Social Capital -- Communities and Neighbourhoods; Housing, communities and neighbourhoods; Housing, communities and neighbourhoods